PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA KELAS X PADA MATA PELAJARAN GEOGRAFI DI SMA NEGERI 1 BATANG ANAI - Tari Arma Yunita; Dedi Hermon (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low learning outcomes of class X students of SMA Negeri 1 Batang Anai, especially in the subject of Geography. From these problems, the problem can be formulated as follows: How are the Geography Learning Outcomes Before the Implementation of the Problem Based Learning Model for Class X at SMA N 1 Batang Anai? How are the Geography Learning Outcomes After the Implementation of the Problem Based Learning Model for Class X at SMA N 1 Batang Anai? How is the Effect of the Problem Based Learning Model on the Geography Learning Outcomes of Class X students at SMA N 1 Batang Anai? The purpose of this study is to determine the Geography Learning Outcomes Before the Implementation of the Problem Based Learning Model for Class X at SMA N 1 Batang Anai, to determine the Geography Learning Outcomes After the Implementation of the Problem Based Learning Model for Class X at SMA N 1 Batang Anai and to determine the Effect of the Problem Based Learning Model on the Geography Learning Outcomes of Class X students at SMA N 1 Batang Anai. The results of statistical tests with the help of SPSS version 18 showed a significance value of 0.001 < alpha significance of 0.05. It can be concluded that Ha is accepted and Ho is rejected, which means that there is an influence of the problem-based learning model on the learning outcomes of class X students in geography subjects at SMA Negeri 1 Batang Anai. The results of this study are expected to be one of the references in developing further research and this study, namely the PBL model, can be used to create innovative learning so that it can provide a good contribution to learning.